Antibacterial synergy-mineralization regulation difunctional nano material as well as preparation method and application thereof

By preparing antibacterial synergistic-mineralization regulating nanomaterials and using tannic acid and hydroxypropyltrimethylammonium chloride chitosan to wrap amorphous calcium phosphate, the problem of the mineralization process being destroyed by the acidic environment during remineralization treatment was solved, and long-term remineralization and antibacterial control of dental hard tissues were achieved, significantly improving the effect of caries treatment.

CN120713863AActive Publication Date: 2025-09-30GUANGXI MEDICAL UNIVERSITY

Patent Information

Application Number
CN202510940224.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-09-30
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

Existing remineralization treatments have the problem of the mineralization process being destroyed by the acidic environment of cariogenic bacteria during the progression of caries, making it difficult to achieve long-term calcium and phosphorus ion release and effective antibacterial control.

Method used

By preparing a dual-functional nanomaterial of "antibacterial synergy-mineralization regulation", plant polyphenol tannic acid and the antibacterial layer hydroxypropyltrimethylammonium chloride chitosan are used to form a cross-linked shell, which wraps amorphous calcium phosphate to achieve electrostatic adsorption and antibacterial functions, thereby promoting the remineralization of dental hard tissue.

Benefits of technology

It achieves long-term release of calcium and phosphorus ions, significantly enhances the mineralization of enamel and dentin, effectively blocks dentinal tubules, significantly reduces secondary caries, and enhances the durability and effectiveness of treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120713863A_ABST
    Figure CN120713863A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial synergy-mineralization regulation difunctional nano material as well as a preparation method and application thereof, and belongs to the technical field of biomedical materials. The preparation method comprises the following steps: mixing a disodium hydrogen phosphate solution and a calcium chloride solution to obtain an amorphous calcium phosphate suspension; mixing the amorphous calcium phosphate suspension with a tannic acid solution to obtain an ACP-TA suspension; and finally, mixing the ACP (at) TA suspension and the hydroxypropyl trimethyl ammonium chloride chitosan solution to obtain the bifunctional nano material. A cross-linked shell is formed through the electrostatic adsorption effect of tannic acid and hydroxypropyl trimethyl ammonium chloride chitosan of the antibacterial layer, amorphous calcium phosphate is effectively wrapped, the crystallization process of amorphous calcium phosphate can be remarkably delayed, long-acting release of calcium and phosphorus ions is ensured, the antibacterial function can be effectively achieved, and the service life of the coating is prolonged. An ideal local microenvironment is provided for remineralization of tooth hard tissue, and finally biomimetic mineralization of enamel and deep mineralization plugging of dentinal tubules are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a "antibacterial synergy-mineralization regulation" dual-functional nanomaterial and its preparation method and application. Background Art

[0002] Caries is listed by the World Health Organization as the third largest chronic non-communicable disease after cancer and cardiovascular disease, which seriously affects human oral health and physical and mental health. In recent years, stopping the development of caries and repairing damaged hard tissues through remineralization methods has become a hot research direction in oral treatment. Remineralization therapy refers to a treatment method that uses remineralization fluid to remineralize demineralized enamel or cementum, restore its hardness, and stop or eliminate early caries lesions. With the continuous deepening of research, its application content has gradually shifted from early caries lesions to experimental treatment of caries at other stages. The principle of remineralization therapy is to deliver a neutral solution containing a certain proportion of calcium and phosphorus ions to the demineralized area of ​​hard tissue, and rely on the relatively high concentration of inorganic ions in the solution to mineralize and accumulate in situ and fill the demineralized gaps, thereby achieving repair of the defective micro-area. Because mineralization undergoes a repair cycle, the mineralizing solution must remain on the tooth surface for a certain period of time to facilitate a steady supply of calcium and phosphate ions to promote mineralization. Furthermore, the solid-phase conversion process of remineralization—the transformation of amorphous calcium phosphate to hydroxyapatite and its subsequent growth—requires a local pH of approximately 6.2. High intakes of sugars or carbohydrates can activate the metabolism of oral cariogenic bacteria, producing large amounts of organic acids that can easily alter the pH, disrupting the dynamic mineralization-demineralization equilibrium on the tooth surface, ultimately gradually destroying the hard tissue and causing caries progression. Therefore, effective remineralization therapy requires, on the one hand, providing high concentrations of calcium and phosphate ions to the demineralized areas of the tooth to achieve long-term mineralization; on the other hand, while promoting remineralization, achieving effective local antibacterial activity within the hard tissue to prevent the continued acid production of cariogenic bacteria, which can lead to increased demineralization and remineralization inhibition. Therefore, the development of dual-functional nanomaterials with "antibacterial synergy and mineralization regulation" and their preparation methods for use in products for both remineralization and antibacterial therapy of hard dental tissues is of great significance. Summary of the Invention

[0003] The purpose of the present invention is to provide a "antibacterial synergy-mineralization regulation" dual-functional nanomaterial and its preparation method and application, so as to solve the problem of dental caries progression caused by the remineralization process in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a "antibacterial synergy-mineralization regulation" dual-functional nanomaterial. The preparation steps of the dual-functional nanomaterial are as follows:

[0006] (1) mixing a disodium hydrogen phosphate solution and a calcium chloride solution to obtain an amorphous calcium phosphate (ACP) suspension;

[0007] (2) mixing the amorphous calcium phosphate suspension and tannic acid (TA) solution to obtain an ACP@TA suspension;

[0008] (3) The ACP@TA suspension and hydroxypropyltrimethylammonium chloride chitosan (HACC) solution were mixed to obtain a dual-functional nanomaterial (ACP@TH).

[0009] Preferably, in step (1), the molar ratio of Ca in the calcium chloride solution to P in the disodium hydrogen phosphate solution is 1.2 to 1.5:1; the concentration of the disodium hydrogen phosphate solution is 0.002 to 0.006 mol / L; and the concentration of the calcium chloride solution is 0.004 to 0.008 mol / L.

[0010] Preferably, the concentration of the tannic acid solution in step (2) is 6-12 mg / mL and the pH value is 8.

[0011] Preferably, the volume ratio of the amorphous calcium phosphate suspension to the tannic acid solution in step (2) is 60:0.10-0.14.

[0012] Preferably, in step (2) and step (3), the mixing temperature is independently 0 to 6° C., and the mixing time is independently 3 to 8 minutes.

[0013] Preferably, the concentration of the hydroxypropyltrimethylammonium chloride chitosan solution in step (3) is 6 to 15 mg / mL.

[0014] Preferably, the volume ratio of the amorphous calcium phosphate suspension to the hydroxypropyltrimethylammonium chloride chitosan solution is 60:3-5.

[0015] Preferably, in step (3), the hydroxypropyltrimethylammonium chloride chitosan solution is added to the ACP@TA suspension in batches during the mixing, and the mixture is incubated for 3 to 8 minutes after each addition.

[0016] The present invention also provides a bifunctional nanomaterial prepared by the above-mentioned preparation method of the "antibacterial synergy-mineralization regulation" bifunctional nanomaterial.

[0017] The present invention also provides a use of the above-mentioned dual-functional nanomaterial in the preparation of a tooth remineralization product or an anti-dentin sensitivity product.

[0018] Antibacterial synergistic remineralization principle:

[0019] The core mechanism of remineralization therapy lies in the targeted replenishment of mineral components required by tooth hard tissues. By delivering mineral ions such as calcium and phosphorus to demineralized areas, a localized, high-concentration mineral environment is created, triggering the biomineralization process. Minerals crystallize and regenerate in an orderly manner within the demineralized matrix, gradually filling the microporous network formed by acid attack, ultimately reestablishing the tooth's natural mineralized structure and restoring its mechanical strength. However, remineralization alone remains challenging. Dental plaque biofilm, as a carrier of the cariogenic microbiome, not only provides a matrix for bacterial adhesion but also creates a permeability barrier through its extracellular polysaccharides, prolonging the acidic microenvironment and interfering with the remineralization process. The key to dental caries treatment lies in balancing the restoration of tooth hard tissue with the effective control of cariogenic bacteria. Antimicrobial therapy inhibits the colonization and proliferation of cariogenic bacteria such as Streptococcus mutans and Lactobacillus acidophilus, reducing plaque biofilm formation and preventing further demineralization at the source. Remineralization therapy, on the other hand, replenishes calcium and phosphorus ions, promoting mineral deposition through a guided mechanism, thereby repairing damaged tooth hard tissues. This dual mechanism combination enables the synergistic effect of remineralization of dental hard tissue and antibacterial treatment, which can not only effectively repair early caries lesions, but also significantly reduce the occurrence of secondary caries and enhance the durability and effectiveness of treatment.

[0020] Beneficial effects of the present invention:

[0021] The present invention uses electrostatic adsorption between plant polyphenol tannins and the antibacterial layer of hydroxypropyltrimethylammonium chloride chitosan to form a cross-linked shell, effectively encapsulating amorphous calcium phosphate. This design not only significantly delays the crystallization process of amorphous calcium phosphate, ensuring long-term calcium and phosphate ion release, but also effectively exerts its antibacterial function through surface adsorption onto the surface of hard dental tissue, providing an ideal local microenvironment for the remineralization of hard dental tissue, ultimately achieving biomimetic mineralization of tooth enamel and deep mineralization and closure of dentinal tubules. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The state picture and optical picture of the ACP@TH nanoassembly of Example 1, wherein A is the state picture and B is the optical picture;

[0023] Figure 2 This is the XRD pattern of the ACP@TH nanoassembly of Example 1;

[0024] Figure 3 TEM crystallization trend diagram of the ACP@TH nanoassembly of Example 1;

[0025] Figure 4 This is the dilution plate counting result of the antibacterial experiment of the control group and the ACP@TH group;

[0026] Figure 5 SEM images of bacterial morphology in the control group and ACP@TH group in the antibacterial experiment;

[0027] Figure 6 These are SEM images of the enamel slices of the control group and the ACP@TH group at different magnifications after 7 days of in vitro mineralization;

[0028] Figure 7 Comparison of Vickers hardness of mineralized enamel in healthy enamel group, control group and ACP@TH group;

[0029] Figure 8 SEM images of the dentin slices in the control group and ACP@TH group after 7 days of in vitro mineralization;

[0030] Figure 9 Comparison of Vickers hardness of mineralized enamel in healthy dentin group, control group and ACP@TH group;

[0031] Figure 10 This is the SEM image of the mineralized dentin slice surface in the ACP@TH group after mechanical friction and acid etching treatment;

[0032] Figure 11 Comparison of the changes in air tightness of mineralized dentin in the control group and ACP@TH group before and after mechanical friction and acid etching treatment;

[0033] Figure 12 SEM images comparing the occlusion effects of dentinal tubules between the control group and the ACP@TH group;

[0034] Figure 13 This is the SEM image of the dentinal tubule blocking depth of the ACP@TH group observed under a low-power microscope. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a "antibacterial synergy-mineralization regulation" dual-functional nanomaterial. The preparation steps of the dual-functional nanomaterial are as follows:

[0036] (1) mixing a disodium hydrogen phosphate solution and a calcium chloride solution to obtain an amorphous calcium phosphate suspension;

[0037] (2) mixing the amorphous calcium phosphate suspension and the tannic acid solution to obtain an ACP@TA suspension;

[0038] (3) The ACP@TA suspension and the hydroxypropyltrimethylammonium chloride chitosan solution were mixed to obtain a dual-functional nanomaterial.

[0039] In the present invention, in step (1), the molar ratio of Ca in the calcium chloride solution to P in the disodium hydrogen phosphate solution is 1.2 to 1.5:1; the concentration of the disodium hydrogen phosphate solution is 0.002 to 0.006 mol / L, preferably 0.003 to 0.005 mol / L, and more preferably 0.004 mol / L; the concentration of the calcium chloride solution is 0.004 to 0.008 mol / L, preferably 0.005 to 0.007 mol / L, and further optimized to 0.006 mol / L.

[0040] As a precursor in the non-classical crystallization pathway of mineralization, amorphous calcium phosphate has excellent bioactivity and the ability to release large amounts of calcium and phosphate ions. It is often added to bone cement, restorative resins, or adhesives as a calcium and phosphate source for remineralization. However, due to its low surface energy and extreme thermodynamic instability, amorphous calcium phosphate easily and spontaneously transforms into the more stable crystalline hydroxyapatite.

[0041] In the present invention, the concentration of the tannic acid solution in step (2) is 6 to 12 mg / mL, preferably 7 to 11 mg / mL, and more preferably 8 to 10 mg / mL; and the pH value is 8.

[0042] Tannic acid is a polyphenolic compound. Its polyhydroxylated structure exhibits antioxidant, metal chelating, free radical scavenging, and protein complexing properties. As a mixture of diphenols and triphenols, tannic acid possesses a unique dendritic structure, which enables it to act as a multidentate ligand to chelate metal ions, thereby forming a three-dimensional, stable metal-phenolic network. This coordination compound is rapidly and stably synthesized, offering a cost-effective and rapid method for preparing functional materials. It also provides an alternative approach for stabilizing amorphous calcium phosphate and slowing crystal growth.

[0043] In the present invention, the volume ratio of the amorphous calcium phosphate suspension to the tannic acid solution is 60:0.10-0.14, preferably 60:0.11-0.13, and more preferably 60:0.12.

[0044] In the present invention, in step (2) and step (3), the mixing temperature is independently 0-6°C, preferably 1-5°C, and more preferably 2-4°C; the mixing time is independently 3-8 min, preferably 4-7 min, and more preferably 5-6 min.

[0045] In the present invention, the concentration of the hydroxypropyltrimethylammonium chloride chitosan solution in step (3) is 6 to 15 mg / mL, preferably 7 to 13 mg / mL, and more preferably 8 to 12 mg / mL.

[0046] Chitosan, the only alkaline polysaccharide discovered in nature to date, possesses excellent biocompatibility, biodegradability, antibacterial properties, and the ability to promote wound healing, making it widely used in medicine, food, functional materials, and other fields. However, due to its high crystallinity and poor water solubility, chitosan can only be dissolved in a few acidic solutions such as acetic acid and hydrochloric acid, which greatly limits its widespread application. Hydroxypropyltrimethylammonium chloride chitosan, a successful example of chitosan modification, introduces quaternary ammonium groups into the chitosan molecular chain through substitution and copolymerization. This modification not only retains the original properties of chitosan but also greatly improves its water solubility and antibacterial properties, playing an important role in treating scars, inhibiting tumor growth, and fighting infections.

[0047] In the present invention, the volume ratio of the amorphous calcium phosphate suspension to the hydroxypropyltrimethylammonium chloride chitosan solution is 60:3-5, preferably 60:4.

[0048] In the present invention, in step (3), the hydroxypropyltrimethylammonium chloride chitosan solution is added to the ACP@TA suspension in batches during the mixing, and the mixture is incubated for 3 to 8 minutes after each addition.

[0049] The present invention also provides a bifunctional nanomaterial prepared by the above-mentioned preparation method of the "antibacterial synergy-mineralization regulation" bifunctional nanomaterial.

[0050] The present invention also provides a use of the above-mentioned dual-functional nanomaterial in the preparation of a tooth remineralization product or an anti-dentin sensitivity product.

[0051] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0052] Example 1

[0053] Under constant temperature cold trap magnetic stirring at 4°C, 30 mL of 0.004 mol / L Na2HPO4 solution and 30 mL of 0.006 mol / L CaCl2 solution were rapidly mixed to obtain an amorphous calcium phosphate suspension; then, 120 μL of 8 mg / mL tannic acid solution (pH = 8) was added to the amorphous calcium phosphate suspension and stirred for 5 minutes to obtain an ACP@TA suspension; finally, 8 mg / mL hydroxypropyltrimethylammonium chloride chitosan solution was added to the ACP@TA suspension in 5 times, 800 μL each time, and each addition was incubated for 5 minutes to obtain a dual-functional nanomaterial, which was recorded as ACP@TH nanoassembly.

[0054] The preparation of ACP@TH nanoassemblies mainly relies on the metal-phenolic network and electrostatic attraction. This unique assembly method provides new ideas and possibilities for the synergistic remineralization and antibacterial treatment of dental hard tissue. During the remineralization process of dental hard tissue, amorphous calcium phosphate, as a mineralization precursor, can gradually transform into HAp on the surface of dental hard tissue, thereby effectively promoting the repair of tooth defects. Tannic acid, as a natural polyphenol compound, binds to Ca in amorphous calcium phosphate through its catechol group. 2+ The metal coordination effect forms a dynamically cross-linked metal-phenolic network, which provides a restricted space for the rapid nucleation of amorphous calcium phosphate, thereby effectively delaying the transformation of amorphous calcium phosphate to crystalline HAp, and ensuring the stability and durability of the material on the tooth surface. Hydroxypropyltrimethylammonium chloride chitosan, as a cationic polymer, has good biocompatibility and antibacterial properties. The quaternary ammonium groups on its molecular chain combine with the negatively charged ACP@TA nanoassembly through electrostatic attraction to form a stable double-layer core-shell structure. This multi-level assembly strategy not only realizes the molecular-level assembly of inorganic-organic components, but the quaternary ammonium groups can also interact with the negative charges on the bacterial cell membrane, thereby destroying the integrity of the bacterial cell membrane and achieving an antibacterial effect. This nanoassembly can not only effectively release antibacterial ingredients and inhibit the growth of caries-causing bacteria in the oral cavity, but also promote the remineralization of dental hard tissue while being antibacterial.

[0055] Example 2

[0056] Under constant temperature cold trap magnetic stirring at 4°C, 30 mL of 0.005 mol / L Na2HPO4 solution and 30 mL of 0.006 mol / L CaCl2 solution were rapidly mixed to obtain an amorphous calcium phosphate suspension; then, 140 μL of 8 mg / mL tannic acid solution (pH = 8) was added to the amorphous calcium phosphate suspension and stirred for 5 minutes to obtain an ACP@TA suspension; finally, 8 mg / mL hydroxypropyltrimethylammonium chloride chitosan solution was added to the ACP@TA suspension in 5 times, 600 μL each time, and each addition was incubated for 5 minutes to obtain a dual-functional nanomaterial, which was recorded as ACP@TH nanoassembly.

[0057] Example 3

[0058] Under constant temperature cold trap magnetic stirring at 4°C, 30 mL of 0.004 mol / L Na2HPO4 solution and 30 mL of 0.006 mol / L CaCl2 solution were rapidly mixed to obtain an amorphous calcium phosphate suspension; then, 100 μL of 8 mg / mL tannic acid solution (pH = 8) was added to the amorphous calcium phosphate suspension and stirred for 5 minutes to obtain an ACP@TA suspension; finally, 8 mg / mL hydroxypropyltrimethylammonium chloride chitosan solution was added to the ACP@TA suspension in 5 times, 1000 μL each time, and each addition was incubated for 5 minutes to obtain a dual-functional nanomaterial, which was recorded as ACP@TH nanoassembly.

[0059] The performance of the ACP@TH nanoassembly of Example 1 was measured:

[0060] (1) Figure 1 The state picture and optical picture of the ACP@TH nanoassembly of Example 1 are shown. Figure 1 It shows that there is no obvious particle aggregation in the ACP@TH nanoassembly, indicating that it has good dispersibility. When irradiated with laser, a bright "pathway" appears in the suspension, further confirming the uniform distribution of the nanoassembly in the solution.

[0061] (2) The freeze-dried ACP@TH nanoassemblies were identified by X-ray diffractometer to confirm their crystallinity. The voltage was 40 kV, 30 mA, and the scanning 2θ range was 10° to 60° with a step size of 0.02°. Figure 2 As shown in Figure 3, the XRD pattern of the ACP@TH nanoassembly exhibits a broad band at approximately 2θ = 30°, which excludes the presence of HAp or other CaP crystalline phases.

[0062] (3) The particle morphology and elemental composition distribution of the ACP@TH nanoassembly of Example 1 were characterized by transmission electron microscopy at 110 kV, and the crystallization trend of the nanoassembly was characterized by selected area electron diffraction. When preparing the TEM sample, the sample solution was first ultrasonically treated, and then 5 μL of the sample solution was dropped onto a carbon-coated copper grid and allowed to stand for 30 seconds. The excess liquid was then removed from the edge of the droplet with filter paper and dried for storage. The characterization results are shown in Figure 2. Figure 3 As shown, the ACP@TH nanoassembly is spherical with a diameter of about 60 nm. It was placed in a 4°C environment until the fifth day before crystallization.

[0063] (4) Ultrapure water and the ACP@TH nanoassembly of Example 1 were used to kill free Streptococcus mutans. The test process was as follows: after the Streptococcus mutans was revived, it was placed in BHI medium at 37°C and 5% CO2. A hydroxyapatite sheet was used to simulate the tooth surface and placed in a 24-well plate. 500 μL of bacterial suspension (10 6 CFU / mL), then an equal volume of sample solution (ultrapure water or ACP@TH, with three replicates per group, ultrapure water as the control group and ACP@TH as the ACP@TH group) was added. After thorough mixing, the cells were incubated at 37°C, 5% CO₂ for 4 hours. After completion of the incubation, the supernatant from each well was collected, and bacterial counts were performed on a dilution plate. The antibacterial activity (R) of the ACP@TH group was analyzed according to the following formula:

[0064] R(%)=(Nc-N) / Nc×100%

[0065] Where Nc represents the number of colonies in the control group, and N represents the number of colonies in the experimental group.

[0066] After 4 hours of antibacterial incubation, scanning electron microscopy was performed simultaneously: the hydroxyapatite sheet was gently rinsed with PBS buffer to remove non-adherent bacteria, and then transferred to a 2.5% glutaraldehyde solution at 4°C for fixation overnight, and then dehydrated with ethanol solutions of different concentration gradients (100%, 90%, 75%, 50% and 25% ethanol solutions, each for 15 minutes). After dehydration, the samples were dried and sprayed with gold, and finally the bacterial morphology of each group was photographed and detected by scanning electron microscopy to observe the morphological differences of Streptococcus mutans in each group. The test results are as follows: Figure 4 、 5 As shown in the figure, the ACP@TH group exhibited significant antibacterial ability, with a sterilization rate of up to 97.3% against free mutans Streptococcus. This group of bacteria also showed obvious shrinkage and deformation under a scanning electron microscope.

[0067] (5) In vitro enamel and dentin mineralization test process: Healthy premolars and third molars without caries, cracks, or defects aged 18 to 25 years were selected to prepare dentin / enamel slices of 4×3×1 mm3, and the surface of the tooth slices was polished with silicon carbide sandpaper. To simulate the acid-etched demineralized tooth surface, the dentin slices were etched with 17% EDTA solution (pH=7) for 8 minutes, and the enamel slices were etched with 37% phosphoric acid for 30 seconds. The acid-etched tooth slices were ultrasonically cleaned in ultrapure water for 10 minutes and finally stored in 0.05% thymol solution at 4°C.

[0068] The tooth pieces were placed in 5 mL of freshly prepared sample solution (ultrapure water or ACP@TH; ultrapure water served as the control group, and ACP@TH served as the ACP@TH group) for 5 minutes. After gently rinsing the surface with ultrapure water, the pieces were immersed in 1.5× simulated body fluid. Each piece was mineralized using 10 mL of solution. The pieces were placed in a 37°C shaker, with the remineralization solution replaced daily for 7 days. After the mineralization experiment, the tooth pieces were removed and sonicated in ultrapure water for 30 seconds to remove loose mineral deposits. The pieces were then dried in a desiccating box overnight for later use.

[0069] The remineralization effect of enamel in each group was characterized by scanning electron microscopy. Figure 6 As shown, only a thin mineral layer was formed on the enamel surface of the control group, and the enamel rod structure before acid etching was still clearly discernible; however, large mineral deposits were observed on the mineralized enamel surface of the ACP@TH group, and it presented a "fish scale" structure similar to that before acid etching.

[0070] Vickers hardness test process: Vickers hardness test was performed on healthy enamel, healthy dentin, mineralized enamel and dentin slices to quantify their hardness changes. Three tooth slices were randomly selected from each group, and 5 points were randomly selected on each tooth slice. A load of 25gf was applied and maintained for 10 seconds to measure the hardness value. The results are as follows Figure 7 and Figure 9 shown. Figure 7 The results showed that the enamel hardness value of the ACP@TH group was significantly higher than that of the control group.

[0071] Figure 8 、 9 The corresponding results are the scanning electron microscopy and Vickers hardness of mineralized dentin. Figure 8 It showed that a continuous and dense mineralized layer was formed on the dentin surface of the ACP@TH group, which completely covered the openings of the dentinal tubules. Figure 9 The results showed that the mechanical strength of mineralized dentin in the ACP@TH group was significantly higher than that in the control group and could be restored to the level of healthy dentin.

[0072] (6) In order to comprehensively evaluate the sealing effect of ACP@TH on dentinal tubules, the study also tested the airtightness of mineralized dentin using a blasting device: the dentin slice was placed between two "O"-shaped rubber rings and fixed, ensuring that the hole in the middle of the rubber ring was completely covered. A pressure gauge and a syringe were connected to the left side through a three-way pipe for precise control and measurement of air pressure; a closed environment was formed on the right side by water droplets. When the syringe injected gas into the device, if the water droplet moved, it indicated that the gas had successfully penetrated the dentin slice. At this time, the value of the pressure gauge could be used to quantify the airtightness of each group of dentin slices.

[0073] The study also subjected the mineralized dentin in each group to mechanical friction and acid etching treatment: the dentin slices in each group were brushed continuously for 20 minutes and then immersed in a 2% EDTA solution for 1 minute. After rinsing and drying, the airtightness of the dentin slices in each group was tested again. Figure 10 As shown in the figure, after the combined treatment of mechanical friction and acid etching, a thin layer of continuous mineral coverage can still be observed on the surface of the mineralized dentin in the ACP@TH group, and its dentinal tubules remain closed, with mineralization blocking the tubular lumen. Figure 11 The airtightness results also showed that the airtightness level of the ACP@TH group remained stable after mechanical friction and acid corrosion tests on mineralized dentin.

[0074] Figure 12 、 13 The effect of ACP@TH mineralization and occlusion of dentinal tubules was tested. It was observed that dense and continuous columnar minerals were formed in the dentinal tubules of the ACP@TH group, and the dentinal tubules were evenly blocked to a depth of about 70μm.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a dual-functional nanomaterial with antibacterial synergy and mineralization regulation, characterized in that: The preparation steps of the dual-functional nanomaterial are as follows: (1) mixing a disodium hydrogen phosphate solution and a calcium chloride solution to obtain an amorphous calcium phosphate suspension; (2) mixing the amorphous calcium phosphate suspension and the tannic acid solution to obtain an ACP@TA suspension; (3) The ACP@TA suspension and the hydroxypropyltrimethylammonium chloride chitosan solution were mixed to obtain a dual-functional nanomaterial.

2. The preparation method of the "antibacterial synergy-mineralization regulation" dual-functional nanomaterial according to claim 1, characterized in that: In step (1), the molar ratio of Ca in the calcium chloride solution to P in the disodium hydrogen phosphate solution is 1.2 to 1.5:1; the concentration of the disodium hydrogen phosphate solution is 0.002 to 0.006 mol / L; and the concentration of the calcium chloride solution is 0.004 to 0.008 mol / L.

3. The preparation method of the "antibacterial synergy-mineralization regulation" dual-functional nanomaterial according to claim 1 or 2, characterized in that: The concentration of the tannic acid solution in step (2) is 6-12 mg / mL, and the pH value is 8.

4. The preparation method of the "antibacterial synergy-mineralization regulation" dual-functional nanomaterial according to claim 1, characterized in that: The volume ratio of the amorphous calcium phosphate suspension to the tannic acid solution in step (2) is 60:0.10-0.

14.

5. The method for preparing the dual-functional nanomaterial of "antibacterial synergy-mineralization regulation" according to claim 2 or 4, characterized in that: In step (2) and step (3), the mixing temperature is independently 0 to 6° C., and the mixing time is independently 3 to 8 minutes.

6. The method for preparing the dual-functional nanomaterial of "antibacterial synergy-mineralization regulation" according to claim 5, characterized in that: The concentration of the hydroxypropyltrimethylammonium chloride chitosan solution in step (3) is 6 to 15 mg / mL.

7. The method for preparing the dual-functional nanomaterial of "antibacterial synergy-mineralization regulation" according to claim 4 or 6, characterized in that: The volume ratio of the amorphous calcium phosphate suspension to the hydroxypropyltrimethylammonium chloride chitosan solution is 60:3-5.

8. The method for preparing the dual-functional nanomaterial of "antibacterial synergy-mineralization regulation" according to claim 1 or 6, characterized in that: In step (3), during the mixing, the hydroxypropyltrimethylammonium chloride chitosan solution is added to the ACP@TA suspension in batches, and incubated for 3 to 8 minutes after each addition.

9. The dual-functional material obtained by the preparation method of the "antibacterial synergy-mineralization regulation" dual-functional nanomaterial according to any one of claims 1 to 8.

10. Use of the dual-functional nanomaterial according to claim 9 in the preparation of tooth remineralization products or anti-dentin sensitivity products.

Citation Information

Patent Citations

  • Delivery system based on nano-hydroxyapatite, preparation method, application, pharmaceutical composition, spray and hydrogel

    CN114652679A

  • Enamel repair material based on tannic acid as well as preparation method and application of enamel repair material

    CN119280397A

  • Collagen cross-linking agents on dental restorative treatment and preventive dentistry

    US20090123581A1

  • Complex for blocking dentinal tubules, reagent for treating dentin hypersensitivity, and use thereof

    WO2025093061A1

Cited By

  • Desensitization medicine for repairing enamel and preparation method thereof

    CN121041210A

  • A desensitizing agent for tooth enamel repair and its preparation method

    CN121041210B

  • Biomimetic mineralization dental cement with antibacterial-mineralization synergistic function as well as preparation method and application of biomimetic mineralization dental cement

    CN121489794A

  • Multifunctional SACP-PEP / TMC film, and preparation method and application thereof

    CN122272377A